Pengembangan Sistem Pertanian Dalam Sektor Beras Untuk Menciptakan Keberlanjutan Pangan - Hanum, Kalista Fauzia; Rajan, Gus; Fadila, Jihan Nur; Revana, Sethela Adhelia; Tisyafianto, Muhamad Rafi Rizqulloh; Desmawan, Deris (LPPM Universitas Labuhanbatu, 2024)
In achieving national food security, the agricultural sector, particularly rice, plays a strategic role. However, there are several challenges in ensuring food security, such as climate change, land degradation, land conversion, and dependence on traditional farming methods. This study focuses on the development of a sustainable rice farming system with an emphasis on adopting modern technology, diversifying superior rice varieties, and strengthening policies and cross-sector collaboration. The research uses a descriptive qualitative approach through literature analysis. The results indicate that food sustainability can be achieved through improved production efficiency, better resource management, and enhancing technology accessibility for smallholder farmers. Recommendations include the implementation of holistic policies to support a sustainable rice farming system.